2013
DOI: 10.1371/journal.pone.0054051
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations in the KCNJ5 Gene in Primary Aldosteronism Patients from Xinjiang, China

Abstract: BackgroundPrimary aldosteronism (PA) is the most common endocrine form of secondary hypertension, and one of the most common subtypes of sporadic PA is aldosterone-producing adenoma (APA). Recently, two somatic mutations of the KCNJ5 gene were implicated in APA, and two germline mutations were associated with familial hyperaldosteronism III.ObjectivesThis case-control study was designed to investigate the relationship between genetic variations in the KCNJ5 gene and sporadic PA patients in Xinjiang, China.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…21 However, this study identified a small increase in the frequency of an SNP in the noncoding 3′-UTR (rs2604204) whose functionality is unknown.…”
Section: Discussionmentioning
confidence: 81%
“…21 However, this study identified a small increase in the frequency of an SNP in the noncoding 3′-UTR (rs2604204) whose functionality is unknown.…”
Section: Discussionmentioning
confidence: 81%
“…15 Interestingly, a recent study investigated the association of KCNJ5 single nucleotide polymorphisms and PA in Chinese patients; one of the polymorphisms, located in the 3′untrans-lated region, was associated with PA in male patients. 16 The functional effect of this polymorphism is unknown; however, an effect on mRNA stability or processing is not expected to cause hyperaldosteronism because variations in KCNJ5 expression (including silencing and overexpression) do not result in major changes in aldosterone secretion and, therefore, the significance of this association needs to be explored more in depth and confirmed in a different population.…”
Section: Hypertensionmentioning
confidence: 99%
“…The role of common KCNJ5 SNPs was also assessed in cohorts of Asian patients with PA and essential hypertension (Li et al 2013. Comparing 235 subjects with sporadic PA to 913 subjects with essential hypertension, Li and coworkers showed that in Chinese population, the minor allele of the KCNJ5 SNP rs2604204, located in the KCNJ5 3′-UTR, was more frequent in males with PA (43.4%) than that in males with essential hypertension (33.3%, P = 0.001) (Li et al 2013), suggesting that KCNJ5 may be involved in the pathogenesis of sporadic PA in Chinese patients.…”
Section: Familial Hyperaldosteronism Type III and Germline Kcnj5 Mutamentioning
confidence: 99%
“…Comparing 235 subjects with sporadic PA to 913 subjects with essential hypertension, Li and coworkers showed that in Chinese population, the minor allele of the KCNJ5 SNP rs2604204, located in the KCNJ5 3′-UTR, was more frequent in males with PA (43.4%) than that in males with essential hypertension (33.3%, P = 0.001) (Li et al 2013), suggesting that KCNJ5 may be involved in the pathogenesis of sporadic PA in Chinese patients. The same SNP was studied in 229 Chinese patients with newly diagnosed essential hypertension .…”
Section: Familial Hyperaldosteronism Type III and Germline Kcnj5 Mutamentioning
confidence: 99%